Fikih Bekerja - Fachri Fachrudin (Institut Agama Islam Sahid Bogor, 2021)
Islam is not a religion that only has a vertical dimension between a servant and his Lord, it is a way of life that regulates all aspects of human life including the relationship between one human being and another human being. This includes Islam governing how a human being maintains the existence of his life in the world. Among the main goals of Islam is hifdz al-mal, namely protecting property which is the right of every human being. From here Islam gives freedom for humans to seek wealth as a tool to fulfill their lives. Islam gives a very high appreciation in work. The fundamental principle in Islam is to do work that is valuable and useful, and vice versa work that is futile and brings harm is declared as forbidden work and is even considered an ally of satan. Also this can be seen in the many verses of the Qur'an and Hadith which call on a Muslim to work.The verses of the Qur'an that regulate ethics at work are the words of Allah ta'ala in QS. Al-Anfaal: 27